TRIAGEM FITOQUÍMICA E AVALIAÇÃO DA ATIVIDADE ANTIOXIDANTE DE Cedrela fissilis VELL. (MELIACEAE) - ADRIANO, Bruno Braga Nogueira; SILVA, Cristiane Aparecida Rosa Pavera; CRUZ, Sorraylla Layanny Alvarenga; ILVA, Ana Francisca Gomes; FEITOSA, Bruno Henrique (ANAIS DO ENIC, 2022)
-